HUBUNGAN PENGETAHUAN BIDAN TERHADAP BERAT BADAN LAHIR BAYI DENGAN RUPTURE PERINEUM DI WILAYAH KERJA PUSKESMAS ATU LINTANG KABUPATEN ACEH TENGAH - Nurlaely HS; Seri Warzukni; Lia Muslima; Riska Nurrahmah (Universitas Prima Indonesia, 2024)
ABSTRACT Perineum rupture is a tear or tear of the tissue between the vulva and anus with an average length of 4 cm. Perineum rupture can occur due to spontaneous tears or episiotomy. Perineum rupture carried out by episiotomy it self must be carried out for indications including: large baby, stiff perineum, birth with abnormalities, delivery using either a porceps or vacuum. This study aims to determine the relationship between midwife knowledge of baby birth weight and the incidence of perineal tears in the Atu Lintang Community Health Center Working Area, Central Aceh Regency. Benefits of research: to increase midwife knowledge of birth weight of baby with perineum rupture. Research methodology: this research is analytical in nature, sampling used total sampling technique, the number of respondents was 30 midwife in the Atu Lintang Community Health Center Working Area. This research was carried out in the Atu Lintang Public Health Center Working Area, Central Aceh Regency. Time of research: Research was carried out on 01 to 09 March 2024. Research measuring tools: Questionnaire consisting of 20 questions about the respondent's knowledge, the data was processed by statistical analysis using the chi square test with the help of the SPSS program. Research results: Of the 19 respondents who experienced perineal rupture during delivery assistance due to the birth weight of the baby with good knowledge, 9 respondents (47.37%), 10 respondents (52.63%), enough 0 respondents (0% ) and 13 respondents who did not experience perineal rupture during delivery assistance due to the birth weight of the baby with good knowledge 7 respondents (63.64%), Fair 4 respondents (36.36%), less than 0 respondents (0%) and obtained a P value = 0.533. Conclusion: that there is no relationship between midwife knowledge of a baby birth weight and the incidence of perineal tears where the value obtained is P value = 0.533. Suggestion: It is hoped that relevant agencies can increase their knowledge and seek information by participating in more capacity building training. Keywords: Knowledge, Midwife, Baby Birth Weight, Perineum Rupture